Epithelial ovarian tumors Analysis of the value of surgery and treatments platinic in a population of 118 cases
Between 1984 and 1994, 118 epithelium ovarían tumours were studied, of which 22 stage / patients 19,3%), 26 stage 11 patients 27,8%), 53 stage 1/1 patients (46,5%), and 13 stage IV patients (11,4%). The mean age was 58 years (range, 14 to 89 years). Histo!ogica!ly, forms found were as fo!low: 84 serous cystomas (71,2%), 14 mucinous cystomas (11,9%), 8 endometrioid tumors, and 7 clear ce!/ tumors. , number=1-2, journal=Cirugía del Uruguay, author=Viola, Alberto and Signorelli, Silvana and Ferrari, araceli and Alonso, Isabel and Barrios, Enrique and Sabini, Graciela and Musé, Ignacio, year=2000, month=Apr., pages=27–35